2006
DOI: 10.2134/agronj2005.0013
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Nitrogen‐15–Labeled Hairy Vetch and Fertilizer Applied to Corn

Abstract: Knowledge of the plant and soil recovery of nitrogen (N) from legume cover-crop residues and fertilizer is needed to improve corn N use efficiency. Nitrogen-15 labeled ammonium sulfate (AS) or hairy vetch (Vicia villosa Roth.) residues were applied at planting or AS at the six-leaf stage (sidedressing) to silage corn (Zea mays L.) grown in 38-cm-diameter by 60-cm-deep microplots containing a Jungdong loam (coarse loamy, mixed, mesic, Typic Udifluvents) in Suwon, Korea. The recovery of the labeled N sources was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 32 publications
5
54
2
Order By: Relevance
“…Rochester & Peoples (2005) found higher BNF in hairy vetch than in this study, contributing to 90 % of the total N in the biomass. Giller & Wilson (1993) and Seo et al (2006) reported hairy vetch N accumulation and biomass production ranging from 100 to 200 kg ha -1 N and from 2.5 to 5.0 Mg ha -1 , respectively, similar to the values found in the present study.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Rochester & Peoples (2005) found higher BNF in hairy vetch than in this study, contributing to 90 % of the total N in the biomass. Giller & Wilson (1993) and Seo et al (2006) reported hairy vetch N accumulation and biomass production ranging from 100 to 200 kg ha -1 N and from 2.5 to 5.0 Mg ha -1 , respectively, similar to the values found in the present study.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, the intensive use of mineral N fertilization for grain crops has been associated with the contamination of natural resources. Consequently, environmentally friendly husbandry practices have been investigated in the last decades, especially the use of legume cover crops to substitute mineral N fertilization partially or even completely (Amado et al, 2002;Seo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the residual N that is incorporated to the soil organic matter has a somewhat long turnover. Other authors have reported low recovery (about 3.5% of the N) by the second crop after sunn hemp cover crop (Silva et al, 2006) or hairy vetch (Vicia villosa Roth) plowed into the soil (Seo et al, 2006). Low recovery of residual N has also been observed for inorganic fertilizer sources: less than 3% of the N derived from fertilizers was taken up by soybeans (Glicine max (L) Merril) (Boaretto et al, 2004), maize (Silva et al, 2006), Seo et al (2006) or sugarcane (Saccharum spp.)…”
Section: ------------------------------------------------------------mentioning
confidence: 95%